Child Support Orders under the Divorce Act, 1985 - Payne, Julien (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1992)
Although spousal support has evoked extensive commentary in diverse law reviews, child support has attracted relatively little attention. The following analysis is intended to remedy that omission. It provides an up-to-date and comprehensive review of the child support under the Divorce Act, 1985. After writing this paper, the author formulated the following ten basic rules of child support and one forecast.